ElasticQ: an active queue management algorithm with flow trust. (2018) - Su, Chenglong; Jin, Guang; Jiang, Xianliang; Niu, Jun
Active queue management (AQM) can improve the network transmission performance and reduce the delay of packets. However, most of previous algorithms cannot achieve the efficiency and fairness simultaneously when high-bandwidth flows exist. In this paper, a novel scheme, named the ElasticQ (elastically fair AQM), is proposed to suppress the high-bandwidth non-responsive flows and enhance the fairness of different flows. Different from previous works, the concept of flow trust is introduced into the design of AQM algorithms to measure the flow's reliability and security effectively. The trust degree of different flows is estimated to decide whether the packets are discarded or not in the proposed scheme with the sample-match mechanism and the packet dropping interval. Simulation experiments results show that ElasticQ could ensure the fairness of various flows, maintain the stability of the queues and decrease the completion time of responsive flows, especially when the responsive flows and non-responsive flows coexist.